2017
DOI: 10.1111/jvp.12473
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling and simulation in animal health. Part III: Using nonlinear mixed‐effects to characterize and quantify variability in drug pharmacokinetics

Abstract: A common feature of human and veterinary pharmacokinetics is the importance of identifying and quantifying the key determinants of between‐patient variability in drug disposition and effects. Some of these attributes are already well known to the field of human pharmacology such as bodyweight, age, or sex, while others are more specific to veterinary medicine, such as species, breed, and social behavior. Identification of these attributes has the potential to allow a better and more tailored use of therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 75 publications
1
56
0
Order By: Relevance
“…best fit the unfit fluorescence data from the same study. During model building, we attempted to balance our model‐building procedure between model performance (empirical fit) and the underlying biology, an approach often referred to as the middle‐out approach …”
Section: Discussionsupporting
confidence: 85%
“…best fit the unfit fluorescence data from the same study. During model building, we attempted to balance our model‐building procedure between model performance (empirical fit) and the underlying biology, an approach often referred to as the middle‐out approach …”
Section: Discussionsupporting
confidence: 85%
“…As the depletion studies were carried out by different labs and with different commercial brands of PPG, the experimental and random variances may be larger than the physiological variability considered in the population PBPK model. The population analysis in current PBPK model did not account for the variabilities between different studies, which could potentially be addressed using the nonlinear mixed‐effect population pharmacokinetic modeling approach (Bon et al, ; Li, Gehring, Lin, & Riviere, ; Mochel et al, ; Mould & Upton, ,; Riviere, Gabrielsson, Fink, & Mochel, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent report from the National Academy of Medicine (64), only one out of ten oncology candidates that appear promising in preclinical mouse models are in fact effective and safe in human clinical trials. This overtly high attrition rate highlights the need for alternative models at the early stage of the Drug Research and Development lifecycle (65), as shown in other therapeutic areas (66)(67)(68)(69)(70)(71).…”
Section: Comparative Oncology: An Opportunity To Accelerate Parallel mentioning
confidence: 99%